METODE IMAGE STREAMING DALAM MENINGKATKAN KREATIVITAS ARANSEMEN MUSIK - Nurharini dan Putri Yanuarita Sutikno, Atip (Universitas Negeri Semarang, 2017)
The Music arrangement has the work done through music performances on stage that doing not only technique but of value artistic. The first observation seen that degree creativity music arrangement subject by PGSD University student are: 1) the low response and appreciation, 2) less motivated, 3). less active for the session answer and question, 4). not self of the learning, 5). ess skill dan creativity of create music arrangement. The purpose of this research were to describe the implementation and creativity music arrangement of PGSD University student through image streaming method. Data collection techniques using observations, documents, field notes, and questionnaire. The results showed that music learning and creativity of PGSD University student using image streaming method has very good improved.